Exploring the impact of cross-cultural training on cultural competence and cultural intelligence: a narrative systematic literature review - Urgun, Deniz; Seidel, Johanna; Vangeli, Eleni; Borges, Mario; de Oliveira, Rita F. (Frontiers in Psychology, 2025)
IntroductionCross-cultural training programs are widely used to enhance cultural competence and cultural intelligence (CQ) across various professional fields. This narrative systematic literature review examines training strategies from various fields to identify the most effective approaches for application in sports. It addresses two key research questions: (1) What training components have been used in the delivery of these training programs? (2) What is their effectiveness in improving cultural intelligence and cultural competence?MethodsA systematic search was conducted to identify qualitative and quantitative studies published between 2000 and 2023. A total of 27 articles met the inclusion criteria. These articles describe the type of training program delivered, the activities performed, and their outcomes on participants’ cultural competence and/or cultural intelligence. Programs were categorized on delivery methods (didactic, experiential, or mixed) and information was extracted on training content, participants, duration, and timing.ResultsMost programs used mixed delivery methods that combined lectures, educational tasks and experiential activities. They showed positive, though not always statistically significant, impact on participants’ cultural competence and/or cultural intelligence.DiscussionIn sports, tailored programs that address culture- and sport-relevant knowledge, skills and communication may help coaches navigate cultural differences.